Komunikasi Strategis Dan Digitalisasi Kelompok Tani Bumi Sinar Mukti Cilengkrang Kabupaten Bandung - Meiyanti Nurchaerani; Ario Pamungkas; Alfian; Syahiid Hidayatullah Rizkika Hartadhi (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Bumi Sinar Mukti Farmers Group faced challenges in optimizing strategic communication and digitalization to strengthen their marketing and organizational management. This community service research aimed to improve members' understanding and skills in utilizing digital media effectively. The methods used included Focus Group Discussions (FGD) to explore members’ needs and expectations, strategic communication training to formulate effective messages, and digitalization assistance through the creation of educational and marketing content. The results showed that members' understanding of the importance of communication strategies increased, as well as their ability to develop structured communication plans and use social media for promotion and market networking. In conclusion, planned digitalization and effective communication strategies became the main strengths of the farmers group in facing market dynamics and enhancing their collective welfare.